Design of The Pyrolysis Furnace for The Alternative Energy - TP Sari; FA Nurmansyah; YC Winursito; I Nugraha (BIOMEJ, 2023)
The pyrolysis furnace material needs to be considered because this component affects the performance of the pyrolysis process. This component material is also essential; the selection of components used is AISI 4340 Normalized Steel, where this material contains Nickel, Chrom, and Molybdenum, with the characteristics of the AISI 4340 Normalized Steel material, which is a steel material that has high hardness properties, can accept significant pressures and forces and is not easily deformed. The method used is Finite Element Analysis (FEA); this method uses a mesh size of 5 mm to get more accurate results. Simulation results of the AISI 4340 Steel Normalized rear axle shaft to determine the values of stress, strain, displacement, and safety factor from temperature variations of 150 °C, 175 °C, 200 °C and 225 °C. The highest maximum stress value occurs at a temperature of 225 °C of 7.339 x 108 Nm. The highest maximum strain value occurs at a temperature of 225 °C of 1.892 x 10 3. The highest displacement value occurs at a temperature of 225 °C of 4.891 x 10 1. The safest safety factor value to use is 1.547 at a temperature of 150 °C. The temperature value is directly proportional to the stress and strain values obtained because the more significant the given temperature value, the greater the stress and strain values.